Petrophysical Property Modifications by Alteration in a Volcanic Sequence at IODP Site U1513, Naturaliste Plateau. Issue 10 (8th October 2021) - Lee, Eun Young; Tejada, Maria Luisa G.; Song, Insun; Chun, Seung Soo; Gier, Susanne; Riquier, Laurent; White, Lloyd T.; Schnetger, Bernhard; Brumsack, Hans‐Jürgen; Jones, Matthew M.; Martinez, Mathieu
Abstract: Petrophysical properties of volcanic rocks are controlled by lithology and subsequent modification by alteration processes. Investigating the linkages, using a range of different techniques, are important to establish how petrophysical properties can inform about the alteration state of volcanic rocks. Here, we compile petrophysical data and correlate these with geochemical and mineralogical analyses acquired from a volcanic sequence on the Naturaliste Plateau, offshore southwest Australia (International Ocean Discovery Program Site U1513). The sequence consists of alternating basalt lava flows and volcaniclastic deposits, intruded by multiple dolerite dikes. Variable alteration intensities from fresh‐slight to strong are quantified using Chemical Index of Alteration. Intervals of slightly altered dikes exhibit low porosity and high values of bulk density, P ‐wave velocity, and thermal conductivity. The increase of alteration intensity corresponds to decreases in bulk density to ∼2 g/cm 3, P ‐wave velocity to ∼2, 000 m/s, thermal conductivity to ∼1.2 W/(m·K) and an increase in porosity up to 50%. Natural Gamma Ray and magnetic susceptibility vary downhole with rock composition and at lithologic boundaries. The distinct variations exhibit a good correlation with primary lithologic characteristics and secondary mineralogical and textural changes attributed to alteration processes. We provide synthesis models of petrophysical variation with alteration intensity. Although differences in primary lithology and alteration type introduce limitations and uncertainties, there is a reasonable applicability of our results to rapidly characterize the alteration intensity and volcanic stratigraphy in volcanic sequences and to calibrate wireline log‐based determinations. This will help others to develop strategies for exploration, drilling, and geophysical research of volcanic rocks. Plain Language Summary: We present the physical properties of rocks comprising a volcanic sequence recovered from the eastern Naturaliste Plateau, offshore southwest Australia. The sequence consists of basalt lava flows and volcaniclastic deposits, which are intruded by multiple dikes. Petrophysical properties of the volcanic rocks are variable with lithology and alteration state. To investigate the linkages, we applied a range of different techniques to correlate petrophysical data with geochemical and mineralogical analyses. The alteration intensity was quantified based on chemical composition into four ranges; fresh‐slight, weak, moderate, and strong. Relatively fresh basalt intervals exhibit low porosity and high values of bulk density, P ‐wave velocity, and thermal conductivity. Increases of alteration intensity correspond to decreases in bulk density to ∼2 g/cm 3, P ‐wave velocity to ∼2, 000 m/s, thermal conductivity to ∼1.2 W/(m·K), and an increase in porosity up to 50%. Natural Gamma Ray and magnetic susceptibility vary with rock composition and at lithologic boundaries. The petrophysical variations were associated with primary lithologic characteristics, secondary mineralogical and textural changes. We provide synthesis models of petrophysical variation with alteration intensity. Our results can be used to rapidly characterize the alteration intensity and volcanic stratigraphy in volcanic sequences and to develop strategies for exploration, drilling, and research of volcanic rocks. Key Points: Petrophysical properties of a volcanic sequence at International Ocean Discovery Program Site U1513 on the Naturaliste Plateau were modified by alteration processes Distinct trends are indicated in correlations of petrophysical variations with alteration intensity and lithologic characteristics This study provides synthesis models of petrophysical parameters corresponding to alteration intensity